THE EFFECTIVENESS OF QUIZIS MEDIA TO IMPROVE READING SKILLS AND KNOWLEDGE ABOUT PRESENT TENSE AND DESCRIBE THING - Vihky Fariskii (Lingustic, Literature and English Education, 2025)
This research investigates the effectiveness of using Quiziz media in improving students' reading skills and knowledge of present tense and descriptive thing. The research results show that using Quiziz significantly improves reading ability and understanding of present tense concepts. This media is also effective in increasing student motivation and interaction. These findings suggest integrating Quiziz into English language learning to improve student learning outcomes.